Feminismo negro: a luta por reconhecimento da mulher negra no Brasil - Almeida, Ceila Sales de (2016)
Brazil is set up legally as a democratic state of law founded on the dignity of the human person, in practice, but is presented as a society cut by gender and race inequalities. Under the influences of a patriarchal matrix Brazilian society constituted a system of sexist social relations, that legitimizes male superiority in the face of the woman. The legacies of the slave past were the basis for ideological construction of racism will Brazilian, who under the guise of a false racial democracy, creates patterns of cultural values in which the black race is Lower and stigmatized. The intersectionality between gender and race oppression black woman is doubly victimized, having their rights violated by racist and sexist oppression through injustice of cultural and economic nature which exclude his dignity and citizenship. These injustices cause social tensions and conflicts and boost the collective political action in the struggle for recognition and redistribution. This dissertation is the problem analysis about the militancy of black feminism in Brazil aiming to measure the size of their struggle for recognition before the overlapping of economic and cultural nature of gender and racial oppressions. As hypothesis intends to prove that the struggle for recognition effected by black feminism has the dimension of dignity by fighting, incorporating the demands of identity and redistribution, which is imposed on the bivalent nature of oppressions perpetrated in the face of black women in Brazil. The method used is the dialectical and theoretical bases are Axel Honneth and Nancy Fraser through the approach of his theories about the recognition and redistribution. They present as objective the analysis of the wave of the feminist movement, the Brazilian racism and black feminism as an instrument of struggle and resistance of the black woman.